A Correlation Study Between Micromechanical Models and Experimental Tests of a Sisal Fiber Composite - Ricardo Janssen Harger da Silva; Joao Gustavo Pereira da Silva; Marco Antonio Luersen; Lucas Freitas Berti (Journal of Natural Fibers)
Fiber-reinforced composite materials are widely used in engineering; however, synthetic components in their composition can cause an environmental impact. Natural fibers, like sisal, offer a more sustainable alternative without compromising beneficial properties. This work aims to analyze micromechanical models and finite element analysis applied to a sisal fiber composite. The Rule of Mixture, Halpin-Tsai, and numerical simulation with a representative volume element (RVE) were used to define materials properties input in finite element simulations of tensile and flexural experiments. Also, the composite, manufactured by vacuum infusion with a polyester resin as a matrix, had its tensile and flexural properties evaluated through standard experiments. The material properties and resulting stress and strain curves were compared to the ones obtained through simulations. The micromechanics models and RVE simulation resulted in elastic modulus varying from 3% to 5.5% compared to experimental results. Additionally, the comparison between the simulated and experimental stress-strain curves for the tensile and flexural tests showed a noticeable divergence. This discrepancy can be attributed to factors such as fiber anisotropy, waviness, the presence of defects, and adhesion failures. Nevertheless, this correlation between micromechanical models and RVE simulations is expected to serve as a useful reference for future studies involving micromechanics, finite element simulations, and engineering applications of sisal fiber-reinforced composites.